Efficacy and Safety of 2 Injection Techniques for Hand Biostimulatory Treatment With Diluted Calcium Hydroxylapatite - Figueredo, Vinícius O; Miot, Hélio A [UNESP]; Soares Dias, Juliana; Nunes, Gisele Jacobino de Barros; Barros de Souza, Marta; Bagatin, Ediléia [UNESP] (Wolters Kluwer, 2020)
BACKGROUND: Calcium hydroxylapatite (CaHA) is effective for dorsal hand rejuvenation. Higher dilutions are used for biostimulation with fewer side effects. OBJECTIVE: To evaluate the efficacy and safety of 2 techniques of diluted CaHA injection for dorsal hand treatment. METHODS: A prospective, evaluator-blinded study was performed to compare (side-to-side) techniques for treating the dorsum of the hands with diluted CaHA: deep fat lamina or subdermal injection. Fifteen women with aging grades between 1 and 3 on the MHGS (Merz hand grading scale) were enrolled and followed up for 24 weeks. The outcomes were a histological analysis of collagen, skin viscoelasticity, high-frequency ultrasound parameters, MHGS score, and the global aesthetic improvement scale (GAIS) score. RESULTS: Improvement in the MHGS and GAIS scores (p < .01) was observed, with no difference between techniques (p > .05). Skin viscoelasticity measures and ultrasonography for dermal parameters improved for both treatments (p < .01). The mean total collagen density increased from the baseline for both techniques (p < .01). Pain during the procedure as well as adverse effects within the follow-up did not differ between treatments (p > .4). The overall satisfaction was 12% greater for the subdermal technique (p < .05). CONCLUSION: Diluted CaHA improves the skin quality of aging hands with a safe profile, without substantial differences between the techniques.